SDN-Honeypot Integration for DDoS Detection Scheme Using Entropy - Irmawati Feren Kilwalaga; Fauzi Dwi Setiawan Sumadi; Syaifuddin Syaifuddin (Universitas Muhammadiyah Malang, 2020)
Limitations on traditional networks contributed to the development of a new paradigm called Software Defined Network (SDN). The separation of control and data plane provides an advantage as well as a security gap on the SDN network because all controls are centralized on the controller so when the compilation of attacks are directed the controller, the controller will be overburdened and eventually dropped. One of the attacks that can be used is the DDoS attack - ICMP Flood. ICMP Flood is an attack intended to overwhelm the target with a large number of ICMP requests. To overcome this problem, this paper proposes detection and mitigation using the Modern Honey Network (MHN) integration in SDN and then makes reactive applications outside the controller using the entropy method. Entropy is a statistical method used to calculate the randomness level of an incoming packet and use header information as a reference for its calculation. In this study, the variables used are the source of IP, the destination of IP and protocol. The results show that detection and mitigation were successfully carried out with an average value of entropy around 10.830. Moreover, CPU usage either in normal packet delivery or attacks showed insignificant impact from the use of entropy. In addition, it can be concluded that the best data collected in 30 seconds in term of the promptness of mitigation flow installation.